Revisiting the applicability of porter’s model to the portuguese manufacturing : a departure from traditional strategies - Lisboa, João Veríssimo (2015)
The purpose of this paper is to analyze the strategies utilized in the Portuguese manufacturing environment, and to compare the results with those of a similar study conducted in 1993. Self-administered surveys were employed and a total sample of 229 firms were used for the analysis. The responses were factor analyzed to establish patterns of strategic behaviours. In comparison with 1993, today’s Portuguese manufacturing firms are using more product development and innovation in order to offer many new customized products to different markets. In most cases, they are capitalizing on flexible manufacturing to achieve more depth and breadth in their product lines.